The effectiveness of promotional strategy for government education program: a case of Multimedia College Kuala Lumpur / Aini Hayati Ahmad - Ahmad, Aini Hayati (Faculty of Business and Management, 2005)
This study evaluates the effectiveness of promotional strategy made by Multimedia College Kuala Lumpur to increase number of student intake. MMCKL has done various promotional activities in order to attract public knowledge about Multimedia College itself. In today's market, many private colleges are providing the best place for tertiary education, so that, this study may help MMCKL to improve the marketing strategy as well as become the best place for education in term of programs offered and facilities. Overall result indicated that generally the public is still not aware about the college and product offered by MMCKL. It was identified that the lack of MMCKL on communication was the main cause of low level of awareness among majority of the public towards the brand and most of them were unsatisfied with the promotion that have been done. However, the quality of the diploma programs offered has a positive feedback from the students or customers. As a conclusion, MMCKL should increase their promotional activities in order to increase the number of student intake.